A disruptive moment? Parliaments, Brexit, and the future of European integration. Issue 4 (2nd October 2021) - Navarro, Julien
ABSTRACT: The withdrawal of the United Kingdom from the European Union (EU) does not only challenge the idea of an ever-deeper integrated union; it also calls into question the very principles on which the European political order has been established. Against this backdrop, the contributions of this Special Issue set out to analyse how parliaments, that is political institutions at the core of democratic systems, have positioned themselves towards and reacted to Brexit. In this introductory article, I first discuss the meaning of Brexit as yet another major political crisis with serious consequences potentially affecting the role and functioning of representative institutions and actors across the EU. Having taken stock of the extant literature on the parliamentarisation and politicisation of the EU, I then detail the cross cutting issues that permeate this Special Issue, namely: How do parliamentarians assess the UK's decision to withdraw from the EU and its consequences? Does Brexit exacerbate existing political divisions or does it generate new cleavages? To what extent have parliaments attempted to and succeeded in influencing Brexit negotiations and their outcome? Finally, the rest of the introductory article provides an overview of the articles constituting this Special Issue.